Evaluasi Program Tahfidz dalam Pembentukan Karakter Peserta Didik di SD N Sibreh Aceh Besar - Fardiyana, Siti; Lailatussaadah, Lailatussaadah; Nurmayuli, Nurmayuli (Pascasarjana IAIN Lhokseumawe, 2024)
The Tahfidz Al-Qur’an program is one of the character education strategies implemented at SDN Sibreh Aceh Besar. This program aims to shape students into religious, disciplined, and morally upright individuals by instilling the habit of Qur’anic memorization from an early age. However, the effectiveness of this program needs to be systematically examined through evaluation, monitoring, and reflection as part of character-based educational management. This study employs a descriptive qualitative approach using purposive sampling. Informants include the principal, tahfidz supervisors, and tahfidz teachers. Data were collected through non-participant observation, semi-structured interviews, and documentation. Data analysis was conducted using the Miles et al. model, which includes data condensation, data display, and conclusion drawing. The findings reveal that the tahfidz program is evaluated through both formative and summative models, with assessment aspects covering attitude, recitation, knowledge, and skills. Monitoring is conducted in layers by the principal, tahfidz teachers, and the education department, using benchmarks such as memorization achievement, discipline, and student character. Reflection is facilitated through personal approaches, outdoor learning activities, and written feedback, enabling students to express their learning experiences authentically. The integration of evaluation, monitoring, and reflection plays a vital role in shaping students’ character holistically. Although the memorization of Juz 30 has not yet reached the expected target, the ongoing mentoring process demonstrates strong potential in cultivating a generation of Qur’an memorizers with noble character.